2008
DOI: 10.1534/genetics.107.079533
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Genetics Literacy Assessment Instrument for Undergraduates

Abstract: There is continued emphasis on increasing and improving genetics education for grades K-12, for medical professionals, and for the general public. Another critical audience is undergraduate students in introductory biology and genetics courses. To improve the learning of genetics, there is a need to first assess students' understanding of genetics concepts and their level of genetics literacy (i.e., genetics knowledge as it relates to, and affects, their lives). We have developed and evaluated a new instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
160
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(175 citation statements)
references
References 28 publications
2
160
0
8
Order By: Relevance
“…Likewise, genetic literacy can also affect public attitudes, interest, and understanding. Genetic literacy refers to one's knowledge and appreciation of basic genetic (and, in the modern context, genomic) principles, as they inform personal decision making and underlie effective participation in public debates on genetic or genomic issues (McInerney, 2002;Bowling et al, 2008). Some studies have reported low levels of public understanding of genetic concepts (e.g., location of genes) and applications (e.g., newborn screening), although participants displayed familiarity with genetic terminology (Lanie et al, 2004;Miller, 2004;Catz et al, 2005;Lea et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, genetic literacy can also affect public attitudes, interest, and understanding. Genetic literacy refers to one's knowledge and appreciation of basic genetic (and, in the modern context, genomic) principles, as they inform personal decision making and underlie effective participation in public debates on genetic or genomic issues (McInerney, 2002;Bowling et al, 2008). Some studies have reported low levels of public understanding of genetic concepts (e.g., location of genes) and applications (e.g., newborn screening), although participants displayed familiarity with genetic terminology (Lanie et al, 2004;Miller, 2004;Catz et al, 2005;Lea et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of ways to probe common conceptual difficulties among genetics students, including multiple-choice questions with written explanations (e.g., Lewis and WoodRobinson 2000; Chattopadhyay 2005), short answer questions (e.g., Mills-Shaw et al 2008; Boujemma et al 2010), and think-aloud student interviews (e.g., Lewis and Kattman 2004). Written responses to questions and think-aloud interviews can provide valuable input on student thinking and dissecting student understanding, but are not always practical to administer and score in a large enrollment undergraduate genetics course.An alternative option for faculty who teach genetics is to use response-validated multiple-choice concept assessments such as the Genetics Concept Assessment (GCA) (Smith et al 2008) and the Genetics Literacy Assessment Instrument (Bowling et al 2008). These instruments are composed of multiple-choice questions designed to document common conceptual difficulties in genetics.…”
mentioning
confidence: 99%
“…An alternative option for faculty who teach genetics is to use response-validated multiple-choice concept assessments such as the Genetics Concept Assessment (GCA) (Smith et al 2008) and the Genetics Literacy Assessment Instrument (Bowling et al 2008). These instruments are composed of multiple-choice questions designed to document common conceptual difficulties in genetics.…”
mentioning
confidence: 99%
“…"Genetic literacy" has been defined as genetics knowledge as it relates to and affects the lives of individuals. 4 Recent studies have suggested that the general public 5 and health care providers 6 have limited genetic literacy. For example, in a large survey of individuals with genetic conditions and their families, 64% of respondents reported having received no genetics education materials from the provider considered most important in the management of their condition.…”
mentioning
confidence: 99%